Interrelations between changes in parameters of HRV, EEG and phagocytosis at patients with chronic pyelonephritis and cholecystitis - Igor L Popovych; Andriy B Kul'chyns'kyi; Anatoliy I Gozhenko; Walery Zukow; Marta M Kovbasnyuk; Tetyana A Korolyshyn (Kazimierz Wielki University, 2018)
Background. Previously we have shown within the immunological homunculus conception that take place causal relationships between induced by balneotherapy changes in parameters of EEG and HRV, on the one hand, and the parameters of humoral and cellular immunity, on the other hand. The purpose of this study is to find out the relationships between induced by balneotherapy changes in parameters of EEG and HRV, on the one hand, and the parameters of phagocytosis, on the other hand. Material and methods. In basal conditions in 33 men and 10 women with chronic pyelonephritis and cholecystitis in remission, we recorded twice, before and after balneotherapy at the spa Truskavets', EEG ("NeuroCom Standard") and HRV ("Cardiolab+VSR"). In blood estimated parameters of phagocytic function of neutrophils against Staphylococcus aureus and Escherichia coli. Results. Judging by the coefficients of canonical correlation, the maximal subordinate nervous regulation is the completeness of phagocytosis of E. coli (R=0,944), whereas the influence of the nervous system on the completeness of phagocytosis Staph. aur. is minimal (R=0,607). With regard to the intensity of phagocytosis, the differences in the strength of nerve influence are expressed less (0,893 vs 0,744), and in relation to the activity of phagocytosis as well as the bactericidal ability of neutrophils, there are no differences between R (0,858 vs 0,857 and 0,831 vs 0,834, respectively). However, significant differences were found between profiles of correlation coefficients between EEG and HRV parameters, on the one hand, and phagocytosis parameters, on the other hand, for representatives of Gram-negative and Gram-positive microbes. Conclusion. In the nervous regulation of phagocytosis by neutrophils of the Gram-negative and Gram-positive microbes are involved the structures that are localized in different parts of the CNS.